Optical characteristics of ordinary and tunable 1D Si photonic crystals in the mid-infrared range - MOORE, ROBERT; PEROVA, TANIA (My University, 2005)
Reflection spectra and photonic band gaps (PBGs) for periodic structures consisting of grooved Si infiltrated with nematic liquid crystals (LCs) E7 have been obtained experimentally and by simulation. Periodically grooved Si matrixes, with lattice periods ranging from 2 to 6 ?m, were fabricated using wet anisotropic etching of (110) Si in an alkaline solution. It is shown theoretically that a substantial shift of PBGs can be obtained when there is a homogeneous alignment of the liquid crystal molecules with respect to the Si walls and, therefore, a change in the LC's refractive index from no to ne during elctro-tuning can be expected. This effect is smaller during thermo-tuning effect when refractive index changed from no to, ni (isotropic LC phase). The simulated reflection spectra are in good agreement with experimental data obtained with a Digilab FTS 6000 FTIR spectrometer in conjunction with a UMA 500 infrared microscope. A shift of the PBG's edges by a factor Deltalambda/lambda=7% was predicted as a result of a thermo-tuning effect and ~10% as a results of electro-tuning effect
PUBLISHED
Keywords: 1D photonic crystals; photonic gap map; birefringence; FTIR microscopy; nematic liquid crystals